2016
DOI: 10.1021/acs.jproteome.6b00663
|View full text |Cite
|
Sign up to set email alerts
|

Secretomic Insight into Glucose Metabolism of Aspergillus brasiliensis in Solid-State Fermentation

Abstract: The genus Aspergillus is ubiquitous in nature and includes various species extensively exploited industrially due to their ability to produce and secrete a variety of enzymes and metabolites. Most processes are performed in submerged fermentation (SmF); however, solid-state fermentation (SSF) offers several advantages, including lower catabolite repression and substrate inhibition and higher productivity and stability of the enzymes produced. This study aimed to explain the improved metabolic behavior of A. br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
23

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 58 publications
0
9
0
23
Order By: Relevance
“…Secretomes of some plant pathogens, mycorrhizal symbiotic fungi, and some micro-ascomycetes, such as Aspergillus , Trichoderma sp., Penicillium sp., Botrytis sp., etc . have also been systematically studied ( Shah et al, 2009 ; Jun et al, 2011 ; Liu et al, 2013 ; Volke-Sepulveda et al, 2016 ). However, studies on macro-ascomycetes are limited.…”
Section: Introductionmentioning
confidence: 99%
“…Secretomes of some plant pathogens, mycorrhizal symbiotic fungi, and some micro-ascomycetes, such as Aspergillus , Trichoderma sp., Penicillium sp., Botrytis sp., etc . have also been systematically studied ( Shah et al, 2009 ; Jun et al, 2011 ; Liu et al, 2013 ; Volke-Sepulveda et al, 2016 ). However, studies on macro-ascomycetes are limited.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the spectral counts obtained after filtering the data with ProteoIQ can be used to evaluate the levels of protein expression and compare the control versus the treated samples. Relative spectral counts can be used to identify upregulation or repression in comparison to control using, for example, the relative spectral abundance factor (RSAF) [36,37]. In the current dataset, we observed that organs and intestines are more likely to be affected by IR exposure than carcasses, since only 39 proteins present in carcasses have an increase or decrease in relative spectral counts two-fold or greater, as compared to 200 in intestines and 264 in organs.…”
Section: Resultsmentioning
confidence: 99%
“…A. oryzae ( Oda et al, 2006 ) secreted 4-6x more protein in SSF. A. brasiliensis ATCC9642 in SSF produces several differentially expressed proteins which lack secretion signals, suggesting an alternative route of secretion such as EVs ( Volke-Sepulveda et al, 2016 ). Dissecting the molecular trafficking of EVs formation would create a novel compartment for enzyme delivery, or bioproduct collection from a culture without specialized transport proteins.…”
Section: Extracellular Vesicles and Biomass Degradationmentioning
confidence: 99%